3D‐quantum interferometer using silicon microring‐embedded gold grating circuit. Issue 10 (30th May 2020) - Arumona, Arumona Edward; Amiri, Iraj Sandegh; Punthawanunt, Suphanchai; Ray, Kanad; Singh, Ghanshyam; Bharti, Gaurav Kumar; Yupapin, Preecha
Abstract: A 3D (three‐dimensional) quantum interferometer consisting of a silicon microring circuit proposed. The interferometer based on the electron spin cloud projections generated by microring‐embedded gold grating. The electron cloud oscillations result from the excitation of the gold grating at the center of the silicon microring by the dark soliton pulse of 1.50 μm center wavelength. The electron cloud spin‐down, spin‐up automatically formed in the two axes ( x, y, respectively) and propagated along the z ‐axis. In this proposal, the sensing mechanism of the circuit is manipulated by varying the reflector gold lengths of the sensing arm. The electron cloud spin coupled and changed by changing the gold lengths. The sensitivity measurement of the 3D quantum interferometer for three gold layer lengths of 100 nm, 500 nm, and 1, 000 nm is (47.62 nm fs −1, ±0.4762 fs −1, ±0.01 nm −1 ), (238.10 nm fs −1, ±0.4762 fs −1, ±0.002 nm −1 ), (476.20 nm fs −1, ±0.4762 fs −1, ±0.001 nm −1 ), respectively. The used circuit parameters are the real ones that can be fabricated by the currently available technology. Moreover, the silicon micro ring circuit acts as a plasmonic antenna, which can apply for wireless quantum communication. The electron cloud spin projection space–time control can apply for quantum cellular automata. Research Highlight: (1) The interferometer resolution of 50 fs is obtained. (2) The 3D interferometer is novel. (3) The system used the practical device parameters, which can be fabricated and tested. (4) It can be applied for bio‐cells interferometer. (5) By using the plasmonic sensor, the wireless (remote sensor) is also possible.